Analisis Hukum Terhadap Korupsi: Penyebab Dan Solusi Pencegahan - Datulangi, Fegi Amelia (Jurnal Ilmu Pendidikan Pancasila, Kewarganegaraan, dan Hukum, 2024)
Corruption is one of the most serious and complex issues in the legal and governmental systems. This study aims to analyze the legal aspects of corruption, including its causes, impacts, and preventive measures. Using a normative-juridical approach, this research examines anti-corruption laws, weaknesses in law enforcement, and the roles of relevant institutions. The causes of corruption include weak oversight, a permissive bureaucratic culture, and a lack of moral integrity. The proposed preventive solutions include strengthening law enforcement, promoting transparency in public administration, implementing anti-corruption education, and enhancing institutional capacities. This study is expected to contribute to the formulation of more effective policies in combating corruption.